Psychoeducation Webinar to Overcoming Stress in COVID-19 Survivors - Dhian Kusumastuti; Ika Yuniar Cahyanti; Endang Retno Surjaningrum; Ilham Nur Alfian (Psychocentrum Review, 2022)
The COVID-19 pandemic had brought several negative impacts on various aspects of life, including causing stress. Stress during the pandemic afflicted all levels of society, including the COVID-19 survivor itself. One of the ways to deal with stress was the provision of psychoeducation. The provision of psychoeducation during the pandemic could be done online in the form of webinars. The effectiveness of the webinar activity was measured by analyzing the differences in the results of stress management knowledge levels and stress levels in the pre-test and post-test sessions. The level of stress management knowledge was measured using a stress management knowledge scale (Guttman split-half Coefficient = .791) while stress was measured using the PSS-10-C scale (α = 0.734). There was an increase in the knowledge score of stress management and a decrease in stress score. It also showed that webinar psychoeducation had a significant effect on the level of knowledge of stress management and stress levels. These results implied that psychoeducation through webinars should be taken into account as a method to overcome COVID-19 Survivor’s stress problems in the midst of a pandemic that required us to limit social contact.